The comparison of the therapeutic massage with the craniosacral method in treating the pain syndrome of the cranial part of the spine - Waldemar Miszewski; Agnieszka Miszewska; Maciej Śniegocki; Zygmunt Siedlecki; Sebastian Grzyb; Joanna Siminska; Katarzyna Pietkun; Iwona Głowacka; Krystyna Nowacka; Wojciech Hagner (Kazimierz Wielki University, 2016)
Miszewski Waldemar, Miszewska Agnieszka, Śniegocki Maciej, Siedlecki Zygmunt, Grzyb Sebastian, Siminska Joanna, Pietkun Katarzyna, Głowacka Iwona, Nowacka Krystyna, Hagner Wojciech. The comparison of the therapeutic massage with the craniosacral method in treating the pain syndrome of the cranial part of the spine. Journal of Education, Health and Sport. 2016;6(4):249-270. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50158 http://ojs.ukw.edu.pl/index.php/johs/article/view/3467   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.     The comparison of the therapeutic massage with the craniosacral method in treating the pain syndrome of the cranial part of the spine   Waldemar Miszewski1, Agnieszka Miszewska3, Maciej Śniegocki2, Zygmunt Siedlecki2, Sebastian Grzyb2, Joanna Siminska1, Katarzyna Pietkun1, Iwona Głowacka1, Krystyna Nowacka1, Wojciech Hagner1   1 Department of Rehabilitation CM UMK Bydgoszcz 2 Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery 3 University of Bydgoszcz, Bydgoszcz   Key words: classic massage, craniosacral therapy, pains, of the cervical part of the spine.   Summary Massage has been used for several thousand years at least, aiming at relief in suffering and decreasing all kinds of ailments, including health problems with the cervical vertebrae. Craniosacral therapy is quite a new method of treatment since it was founded in the first half of the 20th century. It is different from other methods because it treats energetic changes and lessens the pathological tension in the fascia. Whereas, other methods used by physiotherapists begin working with the patient much later, after functional changes have advanced - contractures or structural degenerations, which cannot be fully removed. And the organism will not be able to come back to full efficiency. Pains of the cervical part of the spine occur quite often in modern societies, including the Polish one. What is more, this troubles younger and younger people. The results of the research conducted on two groups of twenty people, which were described by Method T - Student, proved that both the therapeutic massage and the craniosacral therapy are effective ways of treating the pain syndrome of the cranial part of the spine.